2017
DOI: 10.1038/s41598-017-03919-y
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Milk Vetch Improves Plant Growth, Development and 15N Recovery in the Rice-Based Rotation System of South China

Abstract: Chinese milk vetch (CMV) is vital for agriculture and environment in China. A pot experiment combined with 15N labeling (including three treatments: control, no fertilizer N and CMV; 15N-labeled urea alone, 15NU; substituting partial 15NU with CMV, 15NU-M) was conducted to evaluate the impact of CMV on plant growth, development and 15NU recovery in rice-based rotation system. The 15NU-M mitigated oxidative damage by increasing antioxidant enzymes activities and chlorophyll content while decreased malondialdehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
3
14
1
Order By: Relevance
“…Values for RE N in this three-year observation followed the range reported by other studies conducted in paddy soils [12,28,29]. The increase of RE N (Figure 4) in the vetch treatments was the result of a better synchronization between N supply and crop N demand, which was also observed in previous studies [31][32][33]. As reported by Zhu et al [12] and Xie et al [33] from a greenhouse pot trail, vetch combined with urea application resulted in a higher and more persistent soil inorganic N supply than urea applied alone.…”
Section: Effect Of Vetch On Rice N Uptake and N Use Efficiencysupporting
confidence: 88%
See 1 more Smart Citation
“…Values for RE N in this three-year observation followed the range reported by other studies conducted in paddy soils [12,28,29]. The increase of RE N (Figure 4) in the vetch treatments was the result of a better synchronization between N supply and crop N demand, which was also observed in previous studies [31][32][33]. As reported by Zhu et al [12] and Xie et al [33] from a greenhouse pot trail, vetch combined with urea application resulted in a higher and more persistent soil inorganic N supply than urea applied alone.…”
Section: Effect Of Vetch On Rice N Uptake and N Use Efficiencysupporting
confidence: 88%
“…The increase of RE N (Figure 4) in the vetch treatments was the result of a better synchronization between N supply and crop N demand, which was also observed in previous studies [31][32][33]. As reported by Zhu et al [12] and Xie et al [33] from a greenhouse pot trail, vetch combined with urea application resulted in a higher and more persistent soil inorganic N supply than urea applied alone. Furthermore, vetch cropping helped to increase soil microbial activities because vetch covering and incorporation may enhance vetch-microbe interaction by organic C and N input from vetch biomass and root rhizodeposition [23,32].…”
Section: Effect Of Vetch On Rice N Uptake and N Use Efficiencysupporting
confidence: 83%
“…The results indicated limited capacity to maintain rice yield by F 80 treatment without straw and Mv co-incorporation relative to F 100 in the long term. Other studies had shown that, compared with inorganic fertilizer alone, the co-incorporation straw and Mv could reshape the soil microbial community and structure and the involved N cycling in paddy soil, thus mitigating N losses and improving the N utilization efficiency (Gao et al, 2015;Xie et al, 2017). This was in agreement with the increased fertilizer use efficiency in the co-incorporation treatments compared with F 100 (Fig.…”
Section: At Least Twenty Percent Of Inorganic Fertilizer Could Be Redsupporting
confidence: 80%
“…When incorporated together with rice straw, the N-enriched Mv could regulate the quality of returned residues. Such a co-incorporation option could shift the microbial genera community involved in N cycling and mitigate N losses, thus improving the N utilization efficiency (Gao et al, 2015;Xie et al, 2017). A recent study showed that long-term rice-rice-green manure rotation enriches the beneficial bacteria in rice rhizosphere and enhances the nutrient uptake and grain yield .…”
Section: Co-incorporation Of Rice Straw and Greenmentioning
confidence: 99%
“…A recent study, conducted by Xie et al . 13 , investigated the effects of growing Chinese milk vetch on soil and physiological processes governing plant growth of the subsequent rice crop. Their results showed that growing Chinese milk vetch can improve soil N conservation and recovery, increase leaf chlorophyll content, alleviate oxidative damage to plants, and consequently promote biomass production of the subsequent rice crop.…”
Section: Discussionmentioning
confidence: 99%